107 THE EFFECT OF OBESITY ON AORTIC STIFFNESS IS AGE DEPENDANT. (24th May 2013) - Corden, B; Keenan, N G; de Marvao, A S M; Dawes, T J W; DeCesare, A; Diamond, T; Durighel, G; Hughes, A D; Cook, S A; O'Regan, D P
Abstract : Background: Aortic pulse wave velocity (PWV), a measure of central arterial stiffness, is an independent predictor of cardiovascular and all-cause mortality and has been associated with numerous cardiovascular risk factors. However, data on the association between obesity and aortic stiffness have been mixed, with some studies showing a positive association, others a negative association and others apposing effects between the sexes. Methods: 221 adult volunteers (127 female, age range 18–72 years, mean 40.3 years) were recruited via advertisement. Exclusion criteria included a history of cardiovascular-related disease, including hypertension, hypercholesterolaemia or diabetes. Central PWV was measured in the thoracic aorta using MRI. Total body fat mass was measured with multi-frequency bioelectrical impedance analysis. Results: Multiple linear regression analyses showed that, when age, sex and systolic BP were adjusted for, higher body fat composition was associated with lower aortic PWV (p=0.004). These effects were similar for both men and women (p=0.60 for a sex by body composition interaction). Further analysis revealed a significant age by body fat interaction (p<0.001) such that, in young adults obesity predicted a lower PWV whereas in older adults obesity predicted higher PWV. Conclusions: These results show that the effect of obesity on aortic stiffness is age-dependant and are able to consolidate some previously inconsistent findings within the literature. These findings may reflect morphological and physiological differences in obesity at different ages.